(untitled) (Scottish Historical and Archaeological Internet Reports, 2007)
The analysis of the material produced no evidence for domestic activities, such as cereal processing, for the use of plant material as votive offerings or for feasting. Pit contexts contained the highest concentration of burnt peat and heather fragments, while cist contexts contained the highest concentration of cremated bone fragments with very few carbonised plant remains.